Impact of quality of work-life on work-life balance among nurses in Nepal - Paudel, Pushpa (KIC International Journal of Social Science and Management, 2023)
Introduction: This study investigates the impact of the quality of work-life on the work-life balance of nurses in Nepal. By examining the impact of quality of work-life on the equilibrium between professional and personal life, it aims to contribute insights for enhancing the overall well-being of nurses in the Nepalese healthcare sector.Methods: The research design employed a causal-comparative approach to investigate the impact of quality of work life on the work-life balance of nurses. The data was collected using a well-structured five-point Likert scale questionnaire from 200 nurses. Correlation and regression analyses were utilized to draw meaningful insights.Results: The findings of the study reveal that two key factors, namely job security and job satisfaction, significantly influence the work-life balance for nurses. This suggests that nurses who perceive higher job security and experience greater job satisfaction tend to have an improved work-life balance. However, the study did not find any significant impact of job commitment on work-life balance among nurses.Conclusion: The study underscores the pivotal role of job security and job satisfaction in shaping the quality of work life for nurses in Nepal. Higher perceived job security and increased job satisfaction emerge as key factors contributing to an enhanced work environment. Surprisingly, job commitment did not exhibit a significant influence on the quality of work life among nurses in this context. These findings highlight the importance of addressing specific aspects of job security and satisfaction to positively impact the overall work experience of nurses in Nepal.